Development of a Web-Based Internship Licensing System Using the Waterfall Model at the Ministry of Law and Human Rights - Sintia Okta Rina; Resmi Darni; Vera Irma Delianti; Rizkayeni Marta (Universitas Negeri Padang, 2025)
The internship licensing process at the Ministry of Law and Human Rights (Kemenkumham) was previously managed through manual procedures, leading to inefficiencies such as delayed processing, data redundancy, and lack of real-time status tracking. This study aimed to develop a web-based internship licensing system to improve administrative efficiency, transparency, and user experience. The development process employed the waterfall model, covering five stages: requirement analysis, design, development, testing, and maintenance. The system was implemented using Laravel for the backend, Flutter for the frontend, and MySQL for the database. Key features include digital permit submission, weekly and final report uploads, role-based dashboards, and real-time status notifications. System validation involved black-box testing and expert evaluation using a 5-point Likert scale, yielding a 94.66% feasibility score categorized as very feasible. The results demonstrate that the application fulfills core functional requirements and addresses the previously identified administrative limitations. The study concludes that the system is effective for managing internship processes in public institutions. Future improvements include broader system integration with academic information systems and enhanced mobile compatibility.